2012
DOI: 10.3389/fpsyg.2012.00153
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Rapid Decision-Making for Reward

Abstract: Impulsivity is a feature of many brain disorders. Although often defined as the predisposition to act with an inadequate degree of deliberation, forethought, or control, it has proven difficult to measure. This may in part be due to the fact that it is a multifaceted construct, with impulsive decisions potentially arising as a result of a number of underlying mechanisms. Indeed, a “functional” degree of impulsivity may even promote effective behavior in healthy participants in a way that can be advantageous un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 35 publications
5
56
1
Order By: Relevance
“…Impulsive behavior has been suggested to be a result of executive dysfunction caused by behavioral disinhibition (Barkley, 1997). Although impulsivity can be advantageous for healthy individuals under certain circumstances (Burnett Heyes et al, 2012), it can be an indicator of several psychiatric diseases (Moeller et al, 2001). Despite its prominent, negative role affecting a wide variety of everyday activities, the literature reflects numerous inconsistencies in the conceptualization of impulsivity (Depue and Collins, 1999, Moeller, et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Impulsive behavior has been suggested to be a result of executive dysfunction caused by behavioral disinhibition (Barkley, 1997). Although impulsivity can be advantageous for healthy individuals under certain circumstances (Burnett Heyes et al, 2012), it can be an indicator of several psychiatric diseases (Moeller et al, 2001). Despite its prominent, negative role affecting a wide variety of everyday activities, the literature reflects numerous inconsistencies in the conceptualization of impulsivity (Depue and Collins, 1999, Moeller, et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the Traffic Light task, subjects respond to optimize time-sensitive risky rewarding outcomes [ 30 , 31 •]. Subjects view a red light that turns amber and then green, and must respond rapidly to the green Go signal to obtain a reward.…”
Section: Clinicalmentioning
confidence: 99%
“…The outcome measure is the frequency of penalized trials and the overall reward obtained. Anticipatory responding, measured using this task, correlated with the lack of premeditation on the UPPS Impulsive Behaviour Scale, and was negatively correlated with age in healthy volunteers [ 30 ]. The anticipatory response in the Traffic Light task thus occurs in the context of a risky choice, response selection, sensitivity to reward and loss, and capacity for time estimation.…”
Section: Clinicalmentioning
confidence: 99%
“…Thus, it is not surprising that some previous studies using personality inventories reported some positive correlations between “novelty seeking” items and risk-loving behavior dimensions (Kelley et al, 2004). “Impulsivity” was also found to be a contributing factor (Burnett Heyes et al, 2012). These investigations have not been restricted to financial decision making, but include general risk seeking behavior.…”
Section: Introductionmentioning
confidence: 99%